Constructivism in the Primary School Curriculum - Lokanath Mishra (Mizoram University Journal of Humanities & Social Sciences, 2015)
The aim of this study was to examine whether the 5th grade elementary school curricula of Oriya, English, Mathematics, and Environmental science (EVS) courses were congruent with the principles and standards of the constructivist education. Qualitative research methods were used in this small-scale case study which was conducted in an elementary school in oringabalisahi upper primary school, Orissa. The data were gathered through semi-structured interviews and document analyses in the academic year of 2009-2010. The population of interest consisted of 1 BEO, 1 Oriya teacher, 3 English teachers, 4 Mathematics teachers, and 3 Environmental science (EVS) teachers. The findings indicate that the performances of the curricula under investigation are congruent with the principles of the constructivist education. Similarly, the stated and unstated intents of the curricula are congruent with their performances and the standards of the constructivist education.